2013
DOI: 10.1097/sla.0000000000000228
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Role for Surgery for Patients with a Complete Clinical Response after Chemoradiation for Esophageal Cancer? An Intention-to-Treat Case-Control Study

Abstract: Survival of EC patients with a cCR after CRT is better after surgery compared to simply surveillance. In patients of low operative risk and operable disease, surgery should be considered to improve control of locoregional disease and to overcome the inherent limitations of clinical response assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
1
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 34 publications
2
59
1
3
Order By: Relevance
“…The authors compared the outcomes of neoadjuvant CRT followed by surgery and definitive CRT in patients who achieved clinically complete remission (CR) after CRT. 56 Although this study was retrospective in nature, additional surgery significantly improved survival (median, 83 months vs. 31 months; 5-year, 58.9% vs. 33.4%, P ¼ 0.001) as well as DFS (median, 83 months vs. 31 months; 5-year DFS, 57.4% vs. 33.4%, P ¼ 0.001). In addition, all patients were clinically complete responders, but 34.6% of patients who underwent surgery had persistent esophageal tumors or node metastases on the esophagectomy specimens.…”
Section: Issues Related To Good Responders After Crtmentioning
confidence: 89%
See 1 more Smart Citation
“…The authors compared the outcomes of neoadjuvant CRT followed by surgery and definitive CRT in patients who achieved clinically complete remission (CR) after CRT. 56 Although this study was retrospective in nature, additional surgery significantly improved survival (median, 83 months vs. 31 months; 5-year, 58.9% vs. 33.4%, P ¼ 0.001) as well as DFS (median, 83 months vs. 31 months; 5-year DFS, 57.4% vs. 33.4%, P ¼ 0.001). In addition, all patients were clinically complete responders, but 34.6% of patients who underwent surgery had persistent esophageal tumors or node metastases on the esophagectomy specimens.…”
Section: Issues Related To Good Responders After Crtmentioning
confidence: 89%
“…First, the number of randomized trials is only two, which is insufficient to establish a definite conclusion, and one case-control study (conducted by Piessen et al 56 ) reported conflicting results. The authors compared the outcomes of neoadjuvant CRT followed by surgery and definitive CRT in patients who achieved clinically complete remission (CR) after CRT.…”
Section: Issues Related To Good Responders After Crtmentioning
confidence: 95%
“…In fact, a personal decision threshold can be chosen according to the willingness of risking a false-positive result. In the context of predicting pathCR in esophageal cancer, a false-positive finding could result in omission of surgery in a patient with residual disease, which is potentially hazardous (14,33), and therefore the decision threshold should be high (e.g., ;0.9). To evaluate the incremental value of a model including 18 F-FDG PET information, the net benefit (demonstrated on the y-axis) of the model should be higher than the model without that information.…”
Section: Discussionmentioning
confidence: 99%
“…18 The pretherapeutic cTNM classification, performed before any stenting, was based on endoscopic ultrasound and/or CT scan in cases where tumor stenosis precluded full endoscopic ultrasound examination.…”
Section: Pretherapeutic Workupmentioning
confidence: 99%